A Comparison of Senior High School Curriculum Between Indonesia and Japan - Sari, Indah Juwita; El Islami, R. Ahmad Zaky (Jurnal Pendidikan Indonesia Gemilang, 2022)
Indonesia and Japan are two countries that uphold high manners with education from an early age. Indonesia is a large developing countries from Sabang to Merauke, a country with Muslim majorities, and has many tribes and races. On the other side, Japan is one of the countries in Asia which is known for its technological and educational advancements. Japan is a developed country. The aim of this paper is compare the curriculum of the senior high school between Indonesia and Japan. Data collection techniques through internet from the official website of the Ministry of education and culture in Indonesia and Japan and various research reports, journals, and research papers. The data were analyzed critically by looking at the similarities and differences in the curriculum of the two countries and relating them to several influencing factors. There are three component to compare curriculum in senior high school, consist of the curriculum focus in senior high school level, the characteristics of curriculum, and structure curriculum in senior high school level.